Dissociative role for dorsal hippocampus in mediating heroin self‐administration and relapse through CDK5 and RhoB signaling revealed by proteomic analysis. (22nd August 2016) - Chen, Zhong‐Guo; Liu, Xing; Wang, Weisheng; Geng, Fan; Gao, Jing; Gan, Chen‐Ling; Chai, Jing‐Rui; He, Ling; Hu, Gang; Zhou, Hu; Liu, Jing‐Gen
Abstract: Addiction is characterized by drug craving, compulsive drug taking and relapse, which is attributed to aberrant neuroadaptation in brain regions implicated in drug addiction, induced by changes in gene and protein expression in these regions after chronic drug exposure. Accumulating evidence suggests that the dorsal hippocampus (DH) plays an important role in mediating drug‐seeking and drug‐taking behavior and relapse. However, the molecular mechanisms underlying these effects of the DH are unclear. In the present study, we employed a label‐free quantitative proteomic approach to analyze the proteins altered in the DH of heroin self‐administering rats. A total of 4015 proteins were quantified with high confidence, and 361 proteins showed significant differences compared with the saline control group. Among them, cyclin‐dependent kinase 5 (CDK5) and ras homolog family member B (RhoB) were up‐regulated in rats with a history of extended access to heroin. Functionally, inhibition of CDK5 in the DH enhanced heroin self‐administration, indicating that CDK5 signaling in the DH acts as a homeostatic compensatory mechanism to limit heroin‐taking behavior, whereas blockade of the Rho‐Rho kinase (ROCK) pathway attenuated context‐induced heroin relapse, indicating that RhoB signaling in the DH is required for the retrieval (recall) of addiction memory. Our findings suggest that manipulation of CDK5 signaling in the DH may be essential in determining vulnerability to opiate taking, whereas manipulation of RhoB signaling in the DH may be essential in determining vulnerability to relapse. Overall, the present study suggests that the DH can exert dissociative effects on heroin addiction through CDK5 and RhoB signaling. Abstract : Cyclin‐dependent kinase 5 (CDK5) and ras homolog family member B (RhoB) were up‐regulated in the dorsal hippocampus (DH) of rats with a history of extended access to heroin. CDK5 signaling acts as a homeostatic compensatory mechanism to limit heroin‐taking behavior, whereas RhoB signaling is required for the retrieval of addiction memory. The present study suggests that the DH can exert dissociative effects on heroin addiction through CDK5 and RhoB signaling.